Implementasi Metode Kritik Intrinsik dalam Meningkatkan Kemampuan Membaca Al-Quran di Madrasah Tsanawiyah Kota Metro - Kuliyatun Kuliyatun (Edification Journal : Pendidikan Agama Islam, 2020)
Graduates at Mts Muhammadiyah in Metro City have been many successful and working in various fields of life. Mts Muhammadiyah Metro continues to strive to make Madrasas at the forefront. To achieve this all in Mts Muhammadiyah Metro City will improve learning services with effective educational innovations, based on ICT and religion. This research is a descriptive qualitative study carried out at Mts Muhammadiyah in Metro City. For the population of this study were all students of Mts Muhammadiyah metro city class. The results of this study are reading errors in short readings from 30% to 10%, errors in knowing recitation of recitation from 20% to 10%, errors in the smooth distribution of letters from 20% percent to 10% and those who have not memorized hijaiyah letters from 10% live around 5%.